SIFAT FISIK DAN KIMIA SEDIMEN PADA DANAU TONDANO - Vinny V. Moningka; Meldi T.M. Sinolungan; Djoni Kaunang; Rafli Kawulusan (COCOS, 2015)
Abstract Tondano Lake was an important natural resource in Minahasa Regency. There was an important problem, i.e.: lake shallowing through the process of sedimentation. Sediment was mud deposit containing materials through both chemical and biological processes. The purpose of this study was to identify the physical and chemical properties of sediments in Lake Tondano, especially in the eastern part (Eris) and the western part (Remboken). Purposive Sampling Method was in different depth of sampling (Eris 11 m; Remboken 7 m). Parameters observed were physical properties of soil was soil texture, and chemical properties of soil were total nitrogen, available phosphorus, available potassium, C-organic, and pH . Results had showed that, soil physical was silty clay of texture. However, soil chemical were acidity of sediment was slightly acid, i.e. : pH=6.52 (Eris), pH= 6.58 (Remboken), C-organic, Nitrogen and Phosphorus in Eris were higher than in Remboken; and Potassium in Eris and Remboken were very low. Keywords: physical properties, chemical properties, sediment, Tondano Lake.